Pandangan Yusuf Al-Qaradhawi Terhadap Hadis Larangan Perempuan Bepergian Tanpa Mahram Dan Relevansinya Dengan Pelaksanaan Haji Bagi Perempuan - Chalimatus Sadijah (Program Pascasarjana IIQ Jakarta, 2024)
This study aims to explain Yusuf al-Qaradhawi's views on hadiths that prohibit women from traveling without a mahram. This opinion will have implications for the legal status of women's pilgrimage journeys based on Yusuf al-Qaradhawi's understanding of the hadiths. This research is a library study using a descriptive-analytical method. To analyze the data, qualitative content analysis is employed, examining the texts of hadiths and the writings of Yusuf al-Qaradhawi. After analyzing the data, this study concludes that according to al-Qaradhawi, women are permitted to travel without being accompanied by a mahram as long as their safety is guaranteed. This opinion also applies to pilgrimage journeys, as the hadiths of the Prophet do not explicitly specify certain types of travel. Al-Qaradhawi argues that the main purpose of requiring a mahram for women in these hadiths is to ensure their safety.